2021
DOI: 10.1002/jgm.3348
|View full text |Cite
|
Sign up to set email alerts
|

Role of FTO gene polymorphisms in Wilms tumor predisposition: A five‐center case–control study

Abstract: Background: Wilms tumor is the most frequently occurring renal malignancy in pediatrics. The FTO gene exhibits a featured genetic contribution to cancer development.Nonetheless, its single nucleotide polymorphism (SNP) contribution to Wilms tumor remains unknown.Methods: In the present study, 402 Wilms tumor patients and 1198 healthy controls were successfully genotyped for FTO gene SNPs (rs1477196 G>A, rs9939609 T>A, rs7206790 C>G and rs8047395 A>G) using TaqMan SNP genotyping assays. Odds ratios (ORs) and 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Consistent with these findings, Hua et al. reported that in 402 Wilms tumor patients and 1198 healthy controls, the rs8047395 A allele polymorphism in FTO was significantly correlated with elevated FTO expression and increased risk for Wilms tumor, the most common pediatric renal malignancy [27] . Although the expression level of FTO in ccRCC tissues remains divisive, these results suggest FTO might play an important oncogenic role in kidney cancer in both children and adults.…”
Section: Fto Expression and Prognostic Value In Rccmentioning
confidence: 67%
“…Consistent with these findings, Hua et al. reported that in 402 Wilms tumor patients and 1198 healthy controls, the rs8047395 A allele polymorphism in FTO was significantly correlated with elevated FTO expression and increased risk for Wilms tumor, the most common pediatric renal malignancy [27] . Although the expression level of FTO in ccRCC tissues remains divisive, these results suggest FTO might play an important oncogenic role in kidney cancer in both children and adults.…”
Section: Fto Expression and Prognostic Value In Rccmentioning
confidence: 67%
“…Its balance is synergistically regulated by methyltransferases (METTL4) and demethylase (ALKBH1, ALKBH4). Methylation-related studies demonstrated that genetic variants of the methylation-related genes could affect tumor susceptibility 12 , 29 , 30 . Our group previously genotyped 5 N6-methyladenosine (m6A) methylase METTL14 SNPs in 898 neuroblastoma patients and 1734 control samples.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with FTO and ALKBH5, ALKBH1 is a member of the AlkB family, which catalyzes substrate demethylation in Fe (II)- and α-ketoglutarate-dependent manner 32 . Previous research found that the FTO ( ALKBH9 ) gene SNP rs8047395 A>G variant is significantly correlated with Wilms tumor 29 . And the ALKBH5 gene SNPs had a weak impact on hepatoblastoma risk 33 .…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 gene expression was not measured directly with clinical samples due to lack of sample availability. Moreover, the effects of the SNPs (g.4540A > G (rs3740051) and g.4821G > T (rs35995735)) on SIRT1 gene expression need further study, as have been by previous studies [ 62 , 63 ]. In addition, the impact of the SNPs on the onset and progression of T2D needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%